2005
DOI: 10.1192/bjp.187.6.510
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis-induced psychosis and subsequent schizophrenia-spectrum disorders: follow-up study of 535 incident cases

Abstract: Cannabis-induced psychotic disorders are of great clinical and prognostic importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
3
12

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(150 citation statements)
references
References 32 publications
(53 reference statements)
8
125
3
12
Order By: Relevance
“…The former finding was consistent with previous work showing women being more likely than men to develop psychosis following some traumas (76,77). The latter finding was consistent with previous work which has found men being more likely than women to experience psychosis following cannabis use (78). However, our finding that socio-emotional and somatic problems were more common antecedents of voice-hearing in women was a novel finding.…”
Section: Precursors and Adverse Life Experiencessupporting
confidence: 64%
See 1 more Smart Citation
“…The former finding was consistent with previous work showing women being more likely than men to develop psychosis following some traumas (76,77). The latter finding was consistent with previous work which has found men being more likely than women to experience psychosis following cannabis use (78). However, our finding that socio-emotional and somatic problems were more common antecedents of voice-hearing in women was a novel finding.…”
Section: Precursors and Adverse Life Experiencessupporting
confidence: 64%
“…We hypothesized that men and women might interpret voices differently, given the role of socio-cultural factors in the interpretation of voicehearing (75). We also hypothesized that men and women may have different rates of certain antecedents to their voice-hearing, given that women are more likely than men to develop psychosis following traumatic events (76,77), and that men are more likely than women to develop psychosis after using cannabis (78). The second aim of this study was to examine if the affect associated with hearing male voices differed to that associated with hearing female voices.…”
Section: A Quantitative Study Of Women Hearing Voicesmentioning
confidence: 99%
“…In adults, it was found that psychosis induced by stimulants or cannabis abuse often persists or recurs in the absence of continued drug use. 18,46 It has also been shown that methamphetamine abuse in individuals at familial risk causes schizophrenia that persists regardless of whether the drug abuse continues. 16 An extrapolation of these findings 7 The adjusted model includes age, gender, and family history as covariates in addition to controlling for clustering of individuals within families.…”
Section: Discussionmentioning
confidence: 99%
“…Generally this is because I do not share their views on the strength or relevance of the evidence in question. For example they draw attention to a study by Arendt and colleagues showing that amongst a cohort of individuals admitted to hospital with what was labelled at the time as cannabisinduced psychosis, 44.5 % (a proportion Henquet and van Os call a 'great majority ') subsequently attracted a diagnosis of schizophrenia (Arendt et al 2005). This finding could reflect the fact that cannabis use is common amongst people admitted to hospital with a diagnosis of psychotic illness, an observation that is not controversial and which says nothing about direction of causality.…”
Section: The Author Repliesmentioning
confidence: 99%
“…Furthermore, a discussion of observational evidence is biased if it fails to take into account important findings. For example, while Macleod agrees that the acute effects of cannabis include psychotic symptoms, he does not discuss the Danish Psychiatric Central Register followup of such acute intoxications, showing that the great majority were later re-diagnosed with schizophrenia (Arendt et al 2005). Macleod is selective with regard to the scope of the evidence assessing links between cannabis and psychosis.…”
mentioning
confidence: 99%